Normal weight central obesity among Filipinos and its association with cardiovascular diseases: a cross-sectional study. (4th February 2022) - Toledano, B; Yap, E M; Vilela, G
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Philippine Lipid Atherosclerotic Society Background: Normal weight central obesity reflects an increased visceral fat and low lean mass hence its association with cardiovascular diseases Purpose: The study aims to measure the prevalence of normal weight central obesity, to measure its association with cardiovascular diseases and to compare it across the different types of obesity among Filipinos. Methods: The participants were Filipinos aged 20 years old and above who had participated and completed the desired data in the National Nutrition Survey II which employed a stratified multistage sampling that covered the entire Philippine population. The participants were categorized into the following groups: normal weight (NW) (BMI 18.5-24/9 kg/m²) and no central obesity; normal weight with central obesity (NWCO) (WC ≥80cm or WHR ≥ 0.85 for females, WC≥ 90cm or WHR ≥ 0.90 for males); overweight (OW) (BMI ≥ 25-29.9kg/m²); overweight with central obesity (OWCO); obese (OB) (BMI ≥30kg/m²) and obese with central obesity (OBCO). A Binary logistic regression was utilized to determine the odds ratio (OR) and 95% confidence intervals (CI) for hypertension, diabetes and dyslipidemia. Results: A total of 5, 920 participants (2, 883 men and 3, 037 women) were analyzed. The prevalence of NWCO was 39.3%. In comparison to NW, the ORs for hypertension (OR = 1.84, 95% CI, 1.58-2.1, p=.001), diabetes (OR = 2.1, 95% CI 1.5-3.0, p=.001), dyslipidemia (OR = 1.3, 95% CI 1.1-1.5, p=.002), in OBCO hypertension (OR = 2.2, 95% CI 1.7, 2.8, p<.001), diabetes (OR 2.7, 95% CI 1.8, 3.9, p<.001) and in OWCO hypertension (OR = 1.65, 95% CI 1.43-1.9, p=.001), diabetes (OR = 1.58, 95% CI 1.2-2.0, p=.001), dyslipidemia (OR 1.28, 95% CI 1.1-1.5, p=.004) were significantly higher in NWCO Conclusion: Normal weight central obesity is a common finding among Filipinos and is associated with higher risk of hypertension, diabetes, and dyslipidemia in comparison to obese and overweight with or without central obesity.